2021
DOI: 10.1590/s1677-5538.ibju.2020.0443
|View full text |Cite
|
Sign up to set email alerts
|

Influence of treatment access on survival of metastatic renal cell carcinoma in brazilian cancer center

Abstract: Background: Tyrosine kinase inhibitors (TKI) and immunotherapy improved survival in metastatic renal cell carcinoma (mRCC). Disparities in treatment access are present in healthcare systems globally. The aim of this study was to analyze survival outcomes of mRCC patients treated with first-line TKIs in the public (PHS) and private (PrS) health system in a Brazilian Cancer Center. Materials and Methods: Records from all mRCC patients treated with first-line TKIs from 2007-2018 were reviewed retrospectively. Cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Unsurprisingly, healthcare insurance status was an independent prognostic factor for survival in the multivariate analysis. The impact of healthcare insurance on OS has also been described in other upper-middle- and high-income countries ( 29 32 ), and more recently, in other Latin American countries such as Brazil ( 21 , 33 ). These data highlight the importance of access to treatment in an era during which the most effective cancer therapies are extremely expensive and cannot be systematically covered by healthcare systems in LMICs.…”
Section: Discussionmentioning
confidence: 87%
“…Unsurprisingly, healthcare insurance status was an independent prognostic factor for survival in the multivariate analysis. The impact of healthcare insurance on OS has also been described in other upper-middle- and high-income countries ( 29 32 ), and more recently, in other Latin American countries such as Brazil ( 21 , 33 ). These data highlight the importance of access to treatment in an era during which the most effective cancer therapies are extremely expensive and cannot be systematically covered by healthcare systems in LMICs.…”
Section: Discussionmentioning
confidence: 87%
“…A Brazilian study showed that patients with mRCC treated in the government-supported public health system (PHS) had significantly worse overall survival than patients with access to a private health system (PrHS). Overall survival was 16.5 months for PHS patients, compared to 26.5 months for PrHS patients (p = 0.002), which may be due to the worse prognosis and status at the time of presentation among patients who were treated at public institutions, as well as their reduced access to first-and second-line drugs 8 .…”
Section: Discussionmentioning
confidence: 96%
“…FT is also often associated with lower quality of life and treatment non-adherence. FT has been described among patients in countries with universal health coverage and countries that do not have it, although the related costs were different 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Another important prospective, phase 3 trial, the DeFi trial 12 showed that the gamma secretase inhibitor Nirogacestat promoted tumor shrinkage in almost all the patients with objective response rate of 40% and the study demonstrated an improvement in the quality of life of patients treated with Nirogacestat. Disparity and inequity in treatment access is an important barrier that patients with cancer face, 13 especially in the Brazilian health system where there is no officially approved chemotherapy or target agent for DT. This data could partially explain the high frequency of surgery and less indication of systemic treatment.…”
Section: Discussionmentioning
confidence: 99%